Механізм учинення злочинів у сфері надання професійної правничої допомоги - Гусєва, В. О.; Husieva, V. O.; Романаускас, К. А.; Romanauskas, K. A.; Vlada Husieva (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 3 (110). – С. 131-140, 2025)
У статті наголошено, що криміналізація правопорушень у сфері професійної правничої допомоги покликана забезпечити законність, незалежність адвокатури та довіру суспільства до цього інституту. Особливу увагу приділено механізму злочинної діяльності, розвиток уявлень про який пройшов шлях від опису способів учинення до сучасного розуміння його як складної динамічної системи. Встановлено, що цей механізм охоплює взаємодію суб’єкта, потерпілого, обстановки, способу дії та наслідків, посідаючи проміжну позицію між способом учинення та криміналістичною характеристикою. З’ясовано, що злочини проти адвокатів становлять окрему групу правопорушень високої суспільної небезпеки, а дослідження їх механізму є передумовою створення ефективних методик розслідування.

The article emphasises that the legislative criminalisation of criminal offences in the field of professional legal assistance is necessitated by the need to protect the key values of the rule of law – compliance with the law, guaranteeing the independence of the legal profession and maintaining public trust in the legal profession as a self-governing human rights institution. It aims to ensure the stability of the legal aid institution and minimise the risks of external interference that undermines its functioning. In this context, the study of the mechanism of criminal activity is of particular importance, since it is precisely this knowledge that is a prerequisite for the formation of scientifically sound methodological recommendations for the effective investigation of such crimes. It has been determined that the victim occupies a special place in the structure of the mechanism of criminal offences against lawyers, since their professional status, functional duties and behaviour directly determine the nature of the unlawful influence. Another important element is the circumstances of the crime, which form the spatial, temporal, and socio-psychological conditions that determine the specifics of the evidence picture. It is the circumstances and the manner of action that form the basis for constructing investigative versions and further evidence collection. It has been established that, from a criminalistic point of view, offences committed in the field of professional legal assistance constitute a special group, as they affect not only the life, health or property of lawyers, but also the institutional guarantees of the independence of the legal profession and the very possibility of carrying out legal activities. They are characterised by a variety of perpetrators, multiple methods of implementation and a high level of public danger, which undermines not only the rights of the specific victim, but also the authority of the legal profession as a whole. In general, the mechanism of criminal activity in the field of professional legal assistance should be viewed as a complex dynamic system that reflects the cause-and-effect relationships between all participants in the event and the conditions for its implementation. Its thorough study is a necessary prerequisite for the formation of a complete criminalistic characterisation of these offences and the development of specialised methods for their investigation.
Mechanism for Committing Crimes in the Field of Professional Legal Assistance
Keywords: Україна